Refinement via interpretation - Martins, Manuel A. (2009)
Traditional notions of refinement of algebraic specifications, based on signature morphisms, are often too rigid to capture a number of relevant transformations in the context of software design, reuse and adaptation. This paper proposes an alternative notion of specification refinement, building on recent work on logic interpretation. The concept is discussed, its theory partially developed, its use illustrated through a number of examples.